Quantifying patient centered outcomes associated with the use of bilateral endobronchial coil treatment in patients with severe emphysema. (2nd November 2018) - Evans, Rachel; Brutsche, Martin; Busca, Rachele; Deslee, Gaetan; de Soyza, Antony; Fellrath, Jean-Marc; Franzen, Daniel; Hartman, Jorine; Mealing, Stuart; Morton, Tim; Munavvar, Mohammed; Sculpher, Mark; et al.
Abstract: Objective: To determine the impact of endobronchial coils on health-related quality-of-life (HRQoL). This paper utilizes trial data to identify the predictors of HRQoL in patients with severe emphysema, and subsequently estimates the impact of a new treatment on HRQoL (measured by utilities). These utility estimates are used to generate indicative long-term QALY estimates for a range of clinically plausible scenarios as a precursor to cost-effectiveness analyses. Methods: Patient level HRQoL data from RENEW and the National Emphysema Treatment Trial (NETT) were combined and mapped to generic EuroQol 5-dimension health utility questionnaire (EQ-5D) values using a published algorithm. Multilevel statistical models were developed using treatment, time, response, and baseline characteristics (EQ-5D, age, gender, FEV1, lung RV) to predict EQ-5D over time. Lifetime QALY estimates were generated using published survival data from NETT (assuming no impact of treatment on mortality) and four clinically plausible response profiles. Each response profile was combined with assumptions around treatment impact (constant or time varying). Results: After controlling for baseline characteristics, both treatment and response had a statistically significant impact ( p  < .001) on utility (+0.101 and +0.061, respectively). When combined with selected baseline characteristics and time, Coils and Standard of Care (SoC) generated more QALYs than SoC alone in all scenarios, with incremental lifetime benefit ranging from 0.29–0.55 QALYs. Conclusions: Coils and SoC resulted in statistically significant improvements in HRQoL compared to SoC alone in patients with severe emphysema.